2016
DOI: 10.3390/app6120415
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Load Distribution and Dynamic Characteristics of a Thin-Walled Integrated Squirrel-Cage Supporting Roller Bearing

Abstract: Thin-walled integrated flexible support structures are the major trend in the development of current rolling bearing technology. A thin-walled, integrated, squirrel-cage flexible support roller bearing, quasi-dynamic iterative finite element analysis (FEA) model is established in this paper. The FEA model is used to calculate the structural deformation of the thin-wall rings and support structures; the dynamic characteristics of the bearing are analyzed using the noncircular bearing modified quasi-dynamic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Meanwhile, the theoretical expression for the force of ERSFD is built by using the Simpson integral method. Moreover, the ERSFD rotor's equations are established to investigate the rotor's dynamic characteristics [24][25][26][27][28][29][30].…”
Section: . Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the theoretical expression for the force of ERSFD is built by using the Simpson integral method. Moreover, the ERSFD rotor's equations are established to investigate the rotor's dynamic characteristics [24][25][26][27][28][29][30].…”
Section: . Model and Methodsmentioning
confidence: 99%
“…where w c is the angular velocity. δ j is the jth ball element's deformation and it can be given as: The squirrel cage force and elastic ring force can be given as [14,[38][39][40][41]:…”
Section: Motion Equations Of the Ersfd Rotormentioning
confidence: 99%
“…The elastic deformation of the bearing ring will certainly affect its performance, [21][22][23] but there are few researches on its effect on bearing vibration. Alexandre et al, 24 based on the dynamics of high-speed CRBs, found that the flexible ring can reduce the high frequency harmonic vibration of bearings.…”
Section: Introductionmentioning
confidence: 99%